ANALISIS STRATEGI PEMASARAN PADA TRAVEL CV.MOMO PRIMA JAYA SANGATTA - Mega Amelia; Aji Ratna Kusuma; Indra Wahyudi (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2023)
This study aims to analyze marketing strategies through strengths, weaknesses, opportunities and threats, to compile IFAS (Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) and to determine marketing strategies in Travel CV. Momo Prima Jaya Sangatta after being analyzed with SWOT (Strengths, Weaknesses, Opportunities, Threaths). Data was collected through observation and interview methods with the business owner, namely Mr. Herawan as the main rector. The results of this study showed the following values: (1) The results of the EFAS analysis were 3.166 (2) The results of the IFAS analysis obtained a score of 3.568. Based on the results of the SWOT analysis, CV. Momo Prima Jaya Sangatta Travel is in the Quadrant I position using Strengths and Opportunities and the strategy used is the Aggressive S-O Strategy by using internal strengths to take advantage of opportunities as much as possible